Cardiac Regeneration Therapy Using Cell Sheet Technology - Kawamura, Takuji (Drug Delivery System, 2025)
Cardiac diseases are on the increase worldwide, and new treatment approaches that complement existing therapies, such as assisted ventricular assist devices and heart transplants, are being developed. Cell transplantation therapy has gained significant focus as a treatment aimed at regenerating myocardium, and methods using cell sheet technology have progressed from basic research to clinical application. The Department of Cardiovascular Surgery, Osaka University Graduate School of Medicine has been pursuing the clinical application of cell transplantation therapy for heart failure patients, starting with autologous skeletal myoblast cell sheets, followed by iPS cell-derived cardiomyocyte sheets, and then adipose stem cell spray transplantation, which was developed based on cell sheet technology. This report outlines the background and status of the development of myocardial regeneration therapy by cell transplantation in our department.